2011
DOI: 10.1021/tx200457u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the GST-T1 and GST-M1 Null Genotypes Using High Resolution Melting Analysis

Abstract: Glutathione S-transferases, including GST-T1 and GST-M1, are known to be involved in the phase II detoxification pathways for xenobiotics as well as in the metabolism of endogenous compounds. Polymorphisms in these genes have been linked to an increased susceptibility to carcinogenesis and associated with risk factors that predispose to certain inflammatory diseases. In addition, GST-T1 and GST-M1 null genotypes have been shown to be responsible for interindividual variations in metabolism of arsenic, a known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Human GST genes, including glutathione-S-transferase pi 1 ( GSTP1 ), glutathione-S-transferase mu 1 ( GSTM1 ), and glutathione-S-transferase theta 1 ( GSTT1 ), play a crucial role in As metabolism [ 30 ]. These GST genes encode a family of phase II enzymes called glutathione transferases that facilitate the excretion of xenobiotics (e.g., As) by catalyzing their conjugation with the reduced form of glutathione (GSH) [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human GST genes, including glutathione-S-transferase pi 1 ( GSTP1 ), glutathione-S-transferase mu 1 ( GSTM1 ), and glutathione-S-transferase theta 1 ( GSTT1 ), play a crucial role in As metabolism [ 30 ]. These GST genes encode a family of phase II enzymes called glutathione transferases that facilitate the excretion of xenobiotics (e.g., As) by catalyzing their conjugation with the reduced form of glutathione (GSH) [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…GST genes are highly polymorphic [ 36 ]; for example, null alleles of GST genes such as GSTT1 and GSTM1 can lead to a lack of functional enzymes and result in a decrease in detoxification capacity and cell protection from oxidative stress [ 37 , 38 ]. The null genotypes for GSTT1 and GSTM1 have been suggested as genetic factors responsible for inter-individual differences in As metabolism [ 30 ]. For example, previous studies have shown that the GSTM1 null genotype impedes As methylation, which results in increased As retention [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins of the GST family (glutathione S-transferases) are enzymes detoxifying a wide range of hazardous substances, such as reactive oxygen species (ROS) or xenobionts [ 3 ]. These enzymes catalyse the reaction of the conjugation of chemical compounds, of both exogenous and endogenous origin, with glutathione [ 4 , 5 ]. Substances detoxified in this way include lipid peroxidation products, prostaglandins, various types of chemotherapeutics, and the majority of substances belonging to environmental carcinogens, such as heterocyclic aromatic amines [ 5 ].…”
Section: Gst Enzymesmentioning
confidence: 99%
“…These enzymes catalyse the reaction of the conjugation of chemical compounds, of both exogenous and endogenous origin, with glutathione [ 4 , 5 ]. Substances detoxified in this way include lipid peroxidation products, prostaglandins, various types of chemotherapeutics, and the majority of substances belonging to environmental carcinogens, such as heterocyclic aromatic amines [ 5 ]. The conjugation of electrophilic reagents with reduced glutathione, catalysed by GST enzymes, is aimed at limiting the possibilities of hazardous effects of these strongly reactive compounds on vitally important cell components, such as proteins or nucleic acids.…”
Section: Gst Enzymesmentioning
confidence: 99%